Structural Assessment of Ancient Masonries before and during a Rehabilitation Process. Issue 2 (7th February 2020) - Boffill, Y.; Blanco, H.; Lombillo, I.; Villegas, L.
ABSTRACT: The rehabilitation of old buildings requires detailed knowledge of the mechanical characteristics and stress state of the structural elements, which play an important role in the intervention process. In this sense, non-slightly destructive tests can estimate structural characteristics with good precision at relatively low costs. Consequently, this article presents a device, based on the flat jack technique, applied to continuous stress monitoring over time. It also focuses on the onsite determination of service stresses and its continuous monitoring in several masonry buttresses of a historic building, as well as the assessment of the structural safety before, during, and after an intervention process. A brief analysis of the research is performed, and the motivation and the methodology adopted are described. Finally, the evolution of the measurements recorded and the analysis of the results achieved are detailed. The study enabled recommendations to be made to the intervening agents that guarantee structural safety.